Manajemen Konflik dalam Pemanfaatan Bonus Demografi untuk Pembangunan Berkelanjutan di Kementerian Lingkungan Hidup dan Pembangunan Keluarga - Ilham, Rahmatul; Delta Dea Ananta; Syamsir; Mila Nor Elijha; Zahir Fikri Rashief Azwar (Indo-MathEdu Intellectuals Journal, 2025)
This article discusses conflict management in utilizing the demographic bonus as a strategic opportunity for sustainable development in the Ministry of Environment and Family Development. This study uses a descriptive qualitative approach to understand the dynamics of processes, context, and interaction patterns among stakeholders in managing the potential of the productive age group. Research data were obtained from secondary sources, including ministry policy documents, scientific publications, national statistical reports, and strategic documents related to demographic resilience, family planning, human development, and the environment. Data collection was conducted through literature review, document analysis, and examination of official reports. Data analysis employed content analysis techniques through the process of coding, categorization, and meaning extraction. The study results indicate that conflicts are generally triggered by mismatches between institutional capacity, labor market needs, and the quality of the working-age population, and are further reinforced by disparities in access to education, healthcare, and women's economic participation. These findings underscore that integrative conflict management through cross-sector collaboration, governance strengthening, and data-driven planning is key to optimizing the demographic bonus and supporting sustainable development goals